Politics and power in the multinational corporation : the role of institutions, interests and identities - Dorrenbacher, Christoph, 1961-; Geppert, Mike. (Cambridge : Cambridge University Press, 2011)
'The current financial and economic crisis has negatively underlined the vital role of multinational companies (MNCs) in our daily lives. The breakdown and crisis of flagship MNCs, such as Enron, WorldCom, Lehman Brothers, Toyota and General Motors, does not merely reveal the problems of corporate malfeasance and market dysfunction. It also raises important questions, both for the public and the academic community, about the use and misuse of power by MNCs in the wider society, as well as the exercise of power by key actors within internationally operating firms. This book examines how issues of power and politics affect MNCs at three different levels; the macro-level, the meso-level and the micro-level. This wide-ranging analysis shows not only that power matters but also how and why it matters, pointing to the political interactions of key power holders and actors within the MNC, both managers and employees'--
Machine generated contents note: List of figures; List of tables; Foreword Ram Mudambi; Part I. Introduction: 1. Politics and power in the multinational corporation: an introduction Mike Geppert and Christoph D$1'Xr(Brenba;cher; Part II. Politics and Power in MNCs: Institutions, Social Embeddedness and Knowledge: 2. Resource dependence and construction, and macro and micro politics in transnational enterprises and alliances: the case of jet engine manufacturers in Germany Arndt Sorge and Katja Rothe; 3. Bargained globalisation: employment relations providing robust'tool kits' for socio-political strategizing in MNCs in Germany Karen Williams and Mike Geppert; 4. Bridging roles, social skill and embedded knowing in multinational organisations Mark Fenton-O'Creevy, Paul Gooderham, Jean-Luc Cerdin and Rune R{uEBA9}ng; Part III. Politics and Power in MNCs: Headquarters-Subsidiary Relations: 5. Conflict in headquarters-subsidiary relations: a critical literature review and new directions Susanne Blazejewski and Florian Becker-Ritterspach; 6. Intra-organizational turbulences in multinational corporations Andreas Schotter and Paul W. Beamish; 7. Conflicts in headquarters-subsidiary relationships: headquarters-driven charter losses in foreign subsidiaries Christoph D$1'Xr(Brenba;cher and Jens Gammelgaard; 8. Headquarters-subsidiary relationships from a social psychological perspective: how perception gaps concerning the subsidiary's role may lead to conflict Stefan Schmid and Andrea Daniel; Part IV. Politics and Power in MNCs: Role of National Identities and Identity Work: 9. Subsidiary manager socio-political interaction: the impact of host country culture Christopher Williams; 10. Unequal power relations, identity discourse, and cultural distinction drawing in MNCs Sierk Ybema and Hyunghae Byun; 11. National identities in times of organizational globalization: a case study of Russian managers in two Finnish-Russian organizations Alexei Koveshnikov; 12. Contesting social space in the Balkan region: the social dimensions of a'Red' joint venture Mairi Maclean and Graham Hollinshead; Part V. Conclusions: 13. Reflections on the macro-politics of micro-politics Glenn Morgan; Index.s
Keywords: International business enterprises -- Political aspects; Corporate power; BUSINESS & ECONOMICS / International / General